2014
DOI: 10.1615/jlongtermeffmedimplants.2014010918
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Health Disparities: Health Literacy, Cultural Competency, Informed Consent, and Shared Decision Making

Abstract: The factors that contribute to musculoskeletal healthcare disparities may influence the results of studies regarding the long-term outcome of orthopaedic implants. Patient decisions regarding their healthcare and their subsequent outcomes are influenced by health literacy. Providing patients with the information that they need to consent to treatment must be provided in a culturally competent manner. The influence of the physician or healthcare provider on the treatment choice varies depending on the type of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As a concept and a set of practices and methods, HL emerged from two very different roots; one being from medical care with its patient education focus and the other one from the broader public health field with its health promotion perspective [7]. It is a strategy that addresses not only the shortfalls of the individuals in terms of skills and knowledge but also the deficits health services may display in answering the needs of the population (for instance by increasing the readability of consent forms and improving communication skills of health care providers) [8][9][10]. This dual purpose lead to numerous investigations to better capture the scope of HL and also to devise better strategies to improve people's HL, particularly in the clinical context [11][12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…As a concept and a set of practices and methods, HL emerged from two very different roots; one being from medical care with its patient education focus and the other one from the broader public health field with its health promotion perspective [7]. It is a strategy that addresses not only the shortfalls of the individuals in terms of skills and knowledge but also the deficits health services may display in answering the needs of the population (for instance by increasing the readability of consent forms and improving communication skills of health care providers) [8][9][10]. This dual purpose lead to numerous investigations to better capture the scope of HL and also to devise better strategies to improve people's HL, particularly in the clinical context [11][12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…It would be beneficial to discuss potential biases in treatment at the beginning of an SDM conversation. Previous research has found that a patient’s prior knowledge compounds the complexity of the decision-making process, especially for patients with lower literacy rates or those lacking access to high-quality information (McClellan et al., 2014). Furthermore, we found that the discussion of cost is a point of weakness within the process and often overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of these treatment modalities hinges on the engagement and compliance of the patient with their own treatment. Shared decision‐making is a first step in this engagement . This communication can be enhanced with the use of a shared decision‐making tool .…”
Section: Discussionmentioning
confidence: 99%